Exploiting noncovalent interactions in an imine-based covalent organic framework for Quercetin delivery - Vyas, Vijay S.; Vishwakarma, Medhavi; Moudrakovski, Igor; Haase, Frederik; Savasci, Gökcen; Ochsenfeld, Christian; Spatz, Joachim P.; Lotsch, Bettina V. (Advanced materials, 2016)
Covalent organic frameworks (COFs) are a new class of nanoporous polymeric vector showing promise as drug-delivery vehicles with high loading capacity and biocompatibility. The interaction between the carrier and the cargo is specifically tailored on a molecular level by H-bonding. Cell-proliferation studies indicate higher efficacy of the drug in cancer cells by nanocarrier delivery mediated by the COF.